1976
DOI: 10.1111/j.2042-7158.1976.tb02794.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory actions of dapsone and its related biochemistry

Abstract: Dapsone has been examined by two established animal anti-inflammatory models and found to possess anti-inflammatory activity comparable with established non-steroidal anti-inflammatory drugs. Dapsone also possess some biochemical properties common to other anti-inflammatory drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In vitro experiments with other bacteria have shown that the chemotherapeutic agent has sulfonamide-like antimicrobial properties and causes inhibition of the enzyme dihydropteroic acid synthetase (13). However, it seems unlikely that this is the only mechanism (if it is indeed a true in vivo mechanism) since dapsone has been reported to have beneficial effects in non-mycobacterial diseases such as dermatitis herpetiformis (9), generalized pustular psoriasis (19), and leukocytoclastic vasculitis (27) and in some cases of rheumatoid arthritis (26) and Crohn's disease (23). The effects of dapsone therapy observed in these conditions may relate to the anti-inflammatory activity of the drug (22).…”
mentioning
confidence: 99%
“…In vitro experiments with other bacteria have shown that the chemotherapeutic agent has sulfonamide-like antimicrobial properties and causes inhibition of the enzyme dihydropteroic acid synthetase (13). However, it seems unlikely that this is the only mechanism (if it is indeed a true in vivo mechanism) since dapsone has been reported to have beneficial effects in non-mycobacterial diseases such as dermatitis herpetiformis (9), generalized pustular psoriasis (19), and leukocytoclastic vasculitis (27) and in some cases of rheumatoid arthritis (26) and Crohn's disease (23). The effects of dapsone therapy observed in these conditions may relate to the anti-inflammatory activity of the drug (22).…”
mentioning
confidence: 99%
“…In high doses over a prolonged period of time, dapsone appears to suppress the Arthus reaction in guinea pigs (11). Dapsone also shows anti-inflammatory activity comparable with established nonsteroidal anti-inflammatory drugs such as indomethacin (9). Furthermore, an inhibition of lysosomal enzyme release comparable with that of corticosteroids has been shown (12).…”
Section: Introductionmentioning
confidence: 86%
“…It is well known that dapsone (4,4'-diaminodiphenyl sulfone) has a dramatically beneficial effect on DH (3 subcorneal pustular dermatosis (6), generalized pustular psoriasis (7), leukocytoclastic vasculitis (8), and recently, in some cases of rheumatoid arthritis (9) and Crohn's disease (10). Immune complexes have been implicated in the pathogenesis of most of the disorders mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra violetinduced erythema in the guinea pig is an exception although its relevance has never been fully understood. Dapsone, an anti-leprotic agent that possesses antiinflammatory activity (Williams, Capstick, Lewis & Best, 1976;Lewis, Gemmell & Stimson, 1978) inhibited both the early phase (0-1.5 h) and late phase (1.5-4 h) of the response. However, dapsone was more effective at 1.5 h (oral ED50 34 mg/kg) than at 3 h (oral ED50 60 mg/kg).…”
Section: Poster Communicationsmentioning
confidence: 99%